Legal Analysis of the Crime of Attempting to Conduct a Fisheries Business Without a Business License (SIUP): : A Study of the North Jakarta District Court Decision Number 1/Pid.Sus-Prk/2024/PN Jkt.Utr. - Hilda Nur Khaliza; Nurkholim (Fakultas Hukum Universitas Djuanda, 2026)
Indonesia's rich fishery resources are vulnerable to illegal business practices, one of which is the absence of a Fishing Business Permit (SIUP). Unfinished illegal acts (attempts) often go unnoticed, even though they have a significant preventive impact. This study aims to analyze and understand the application of attempted crimes (poging) in the context of fisheries crimes without an SIUP and to analyze the criminal liability imposed on perpetrators based on the North Jakarta District Court Decision Number 1/Pid.Sus-Prk/2024/PN Jkt.Utr. This study uses a normative legal research method with descriptive analytical research specifications. The data sources used are primary legal materials in the form of legislation (Criminal Code and Fisheries Law) and court decisions, as well as secondary legal materials in the form of literature and criminal law doctrine. The approaches used are case studies and a legislative approach. The concept of attempted crime (Article 53 of the Criminal Code) has been proven to be effectively applicable in cases of unfinished fisheries crimes. The North Jakarta District Court's decision shows that the elements of intent, commencement of execution, and incompleteness due to external factors (arrest) have been fulfilled, so that fisheries crimes can be prosecuted from the initial stage. The perpetrator was also proven to have fulfilled the element of fault (mens rea) in the form of intent because he acted with full awareness that his actions were against the law, thus making him liable for criminal responsibility. It is recommended that authorities increase patrols and surveillance, and that the government simplify the SIUP licensing procedure to reduce the motivation for illegal activities.